Determination of eight polyphenols and pantothenic acid in extra‐virgin olive oil samples by a simple, fast, high‐throughput and sensitive ultra high performance liquid chromatography with tandem mass spectrometry method. Issue 18 (13th August 2015) - Gosetti, Fabio; Bolfi, Bianca; Manfredi, Marcello; Calabrese, Giorgio; Marengo, Emilio
Abstract : A new ultra high performance liquid chromatography coupled with tandem mass spectrometry method for a fast and sensitive determination of eight polyphenols (hydroxytyrosol, catechin, epicatechin, epigallocatechin gallate, oleuropein, quercetin, rutin, tyrosol) and panthotenic acid in extra‐virgin olive oil was developed. The method does not require long sample pre‐treatment and presents the lowest limit of detection and limit of quantitation values present in literature. Inter‐ and intra‐day variability, linear dynamic range of the calibration curve, recovery and matrix effect were also determined and investigated. The method was applied to several oil samples of different type and origin. Given its accuracy, precision and rapidity, the method is characterized by an interestingly high throughput, reliability, and sensitivity.